A method to improve fishing selectivity through age targeted fishing using life stage distribution modelling - Burns, Neil M. (PLoS One, 2019)
Understanding spatial distributions of fish species is important to those seeking to manage fisheries and advise on marine developments. Distribution patterns, habitat use, and aggregative behaviour often vary throughout the life cycle and can increase the vulnerability of certain life stages to anthropogenic impacts. Here we investigate distribution changes during the life cycle of whiting (Merlangius merlangus) to the west of the UK. Density distributions for age-0, age-1 and mature fish were modelled as functions of environmental variables using generalised additive mixed effects models. The greatest densities of age-0 whiting occurred over finer sediments where temperatures were between 12 to 13°C. Age-0 whiting densities decreased with increasing depth. Higher densities of age-1 whiting were also associated with fine sediments and peaked at 60 m, but this influence was also dependent on proximity to shore. Mature fish, while showing no association with any particular sediment type, were strongly associated with depths >60 m. Geostatistical aggregation curves were used to classify space use and showed persistent aggregations of age-0 whiting occupying inshore waters while age-1 and mature fish were more dispersed and differed among years. The differences in distributions among life stages suggested a general coastal to offshore shift as cohorts developed with mature whiting mainly occupying deep offshore waters. The spatial dynamics and areas of persistent life stage aggregation identified here could enable informed targeting and avoidance of specific age-class whiting to aid bycatch reduction. Given that landing obligation legislation is counterproductive unless it encourages greater fishing selectivity, the ability to avoid this species and undersized individuals would aid conservation measures and fishermen alike.